Microstructure and Electrical Properties of Low-temperature Solution-processed Sol-gel KNN Thin Films - Hien, Vu Thu; Minh Phuong, Nguyen Thi (VNU Journal of Science: Mathematics - Physics, 2020)
We report on an environmentally friendly and versatile chemical solution deposition route to K 0.5 Na 0.5 NbO 3 (KNN) thin films. The excess amounts of K and Na in KNN precursor solutions was found to be strong influence on perovskite KNN single-phase thin films. It was revealed from Raman spectroscopic analysis data that a change in scattering mode was observed for the KNN thin films fabricated under various processing conditions. This change was due to the chemical composition fluctuation of K and Na in the KNN thin films during heat treatment. The leakage current and ferroelectric properties of the thin films were strongly affected by the excess amounts of K and Na as well. KNN thin films with 20 mol% excess K and Na exhibited a leaky ferroelectric polarization–electric field (P–E) hysteresis. Leakage current density of the film was 3.85´10 -8 A/cm 2 at applied field of -60 kV/cm.